Habitat Use by Reintroduced Mountain Quail - Michael Pope; John A. Crawford (National Quail Symposium Proceedings, 2017)
Mountain quail (Oreortyx pictus) have declined in much of the Intermountain Region of the western United States. Many areas that once supported these birds now seemingly lack necessary food and cover, especially in critical riparian zones. Additionally, mountain quail appear to need periodic disturbance (fire, moderate grazing, etc.) to provide adequate forage and nesting areas. If mountain quail do not readily occupy suitable habitats, either because of restricted movements or because of habitat discontinuities, it may be necessary to stock birds in order to restore populations. In September 1995, we began a restoration program with the objective of reintroducing mountain quail into former ranges in eastern Oregon and Washington. In the winter of 1996–1997, we released 17 radio-marked birds into a drainage in Hell's Canyon as a pilot study to determine habitat use, survival estimates, and movement patterns. An additional 40 radio-marked birds were released during spring 1998 to determine habitat use, nesting success, and brood survival.